PEMBUATAN BIOETANOL SECARA ENZIMATIS DARI LIMBAH BATANG SAWIT (Elaeis guineensis) DENGAN PENAMBAHAN SURFAKTAN - Ina Winarni; Sri Komarayati; T. Beuna Bardant (BRIN Publishing, 2016)
Biomass is an alternative potential raw materials for biofuels or bioethanol production. This paper studies bioethanol production of theoil palm trunk waste. The trunk was divided intothree parts; parenchym(P),vascular bundle (VB) and the mixtureof parenchyma and vascular bundle (PVB). Results show that sugar content reduction of all treatments (using surfactant) before fermentation is higher than that without surfactant (control) at 10 and 15 FPU/g substrateof cellulase concentration. The highest ethanol content (1.63%) was recorded from parenchyma with 15 FPU/g substrate of cellulase concentration.